A Study on Teacher Competencies of Pre-service Science Teachers - Acarli, Dilek Sultan; Yaman Kasap, Melek (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2022)
In this research designed in survey model, teacher competencies of pre-service science teachers were examined under 4 headings including methodological, social, and personal competencies (Frey, 2008). As a data collection tool, a questionnaire consisting of a total of 226 items questioning the areas of competence was used. The sample of the study consisted of 602 pre-service teachers who continued their education in science, mathematics, biology, chemistry, and physics education programs. In general, it was determined that the perceptions of pre-service teachers about their professional competencies were high. Confirmatory factor analysis was performed to determine the compatibility of the four-factor structure of teacher competencies with the sample data. Among the teacher competence areas, path analysis by Frey (2008) was performed to test the status of correlations in the sample. As a result of the path analysis, it was seen that the proposed theoretical model worked largely in the sample. Examining the relationships among the competence areas, it was determined that methodological competence had a very high effect on social competence and a moderate effect on personal competence. It was concluded that the competence related to the teaching process affected social competence at a low level and personal competence at a moderate level. In addition, a very high relationship was calculated between methodological competence and competence areas related to the teaching process.